2014
DOI: 10.11648/j.ajls.s.2014020602.12
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Volatile and Non-Volatile Compounds of Trichoderma spp. on Botrytis Fabae the Causative Agent of Faba Bean Chocolate Spot

Abstract: Antagonistic fungi naturally occurring on faba bean leaf surface were isolated and evaluated for their activity as bioagents for Botrytis fabae the causative agent of chocolate spot disease. Thirty isolates were purified and identified as 26 isolates of Trichoderma species (Trichoderma album, T. aureoviride , T. hamatum, T. harzianum and T. viride) and 4 isolates belonging to the genera of Cladosporium, Gliocladium, Epicoccum and Paecilomyces. The inhibitory effect of these isolates was assessed in vitro again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In their research, Barakat et al. (2014) reported a 50% inhibition of B. fabae when working with a strain of T. album . Silva et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their research, Barakat et al. (2014) reported a 50% inhibition of B. fabae when working with a strain of T. album . Silva et al.…”
Section: Resultsmentioning
confidence: 99%
“…In their research, Barakat et al (2014) reported a 50% inhibition of B. fabae when working with a strain of T. album. Silva et al (2021) reported a 35% inhibition of S. sclerotiorum when working with a strain of T. azevedoi CEN1241.…”
Section: Volatile Metabolitesmentioning
confidence: 99%
“…Giza 716 were planted in pots (30 cm in diameter, three replicates of each cultivar). In order to preserve high relative humidity, the established plants were sprayed with the appropriate isolate's spore suspension 45 days after sowing and covered with polyethylene bags for 24 hours (Barakat et al, 2014). In this regard, biological control treatments were sprayed at the suggested concentrations ve days after the pathogen was arti cially inoculated.…”
Section: Antagonistic Effect Of Different Antagonists Against Botryti...mentioning
confidence: 99%
“…Similarly, the fungal phytopathogen Alternaria alternata emits volatiles that promote growth and flowering in Arabidopsis thaliana (Sánchez-López et al, 2016). Furthermore, from the perspective of biocontrol, numerous microbial BVOCs emitted by phyllospheric microbes showed antagonistic activities towards various foliar phytopathogens (Barakat et al, 2014;Thakur & Harsh, 2014). Epiphytic microbes from plant phyllosphere play a role in mediating tripartite interactions (Figure 1), for example plant-arthropod interactions (Noman et al, 2020).…”
Section: Epi-microbial Bvocs In Promoting Growth Providing Associational Defence and Mediating Tripartite Interactionsmentioning
confidence: 99%